(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
The article considers the technological aspects of ultrafiltration in membrane systems for cleaning and concentrating juices. The main process parameters, fouling problems and modern approaches to increasing efficiency are analyzed. The prospects for using innovative membrane materials and combined technologies are determined. The directions of process optimization for improving the quality of juice products and reducing energy costs are substantiated.